Kinesiotherapeutic Treatment in the Case of the Multiple Sclerosis — Case Report - Zuzana Hudáková; Lada Cetlová; Vlasta Dvořáková (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. Multiple sclerosis is understood to be an autoimmune disorder causing progressive inflammatory damage to myelin and finally destruction of axons. It is characterized by diffused deposits of demyelination which cause trespassing of the nervous impulses transfer. These deposits can trigger numerous symptoms including paresis, nystagmus or dysarthria, whereby their character depends on the place of the lesion in the central nervous system (CNS). As a demyelinational disease, multiple sclerosis is incurable and we still do not know the exact reason for its rise. The non-pharmacological treatment of multiple sclerosis includes also rehabilitation as well as appropriate lifestyle which are really very important in case of these patients. Case Report. The paper describes the case of a 68-year-old woman diagnosed with multiple sclerosis in whom weekly therapy and rehabilitation programme have been proposed. Also, recommendations for long-term rehabilitation have been submitted. Discussion. The plan of rehabilitation always corresponds to the degree of classification of the patient’s handicap assessed by rating scales. Conclusions. Patients’ impressions after the training in case of the multiple sclerosis vary, but long-term exercising positively influences their overall health condition. We recommend to the patients doing exercise which ought to be done as long as their health condition allows to do it. The patients can obtain here a lot of relevant information which is connected with their lives. (JNNN 2015;4(2):69–75)